The Effect of Leverage and Firm Size to Profitability of Public Manufacturing Companies In Indonesia - Kartikasari, Dwi; Merianti, Marisa (International Journal of Economics and Financial Issues, 2016)
This study aimed to analyze the effect of leverage and the size of a company to its profitability. Data were obtained from the financial statements of 100 qualified manufacturing companies listed in Indonesia Stock Exchange in the period of 2009 to 2014. Leverage was measured by debt ratio, while firm size was measured by total assets and total sales, and profitability by return on assets. Panel data regression analysis was implemented to analyze the influence of independent variables to the dependent variable. The most suitable panel data regression model in this study was a fixed effect model. The study found that the debt ratio had a significant positive effect on profitability while total assets had a significant negative impact. In contrast, total sales had statistically insignificant effect to the profitability of the companies. Keywords: Leverage, Firm Size, Profitability JEL Classification: M210